ORGANIZATIONAL AND ECONOMIC SUPPORT FOR THE MANAGEMENT OF INVESTMENT PROJECT IN THE SYSTEM OF FORMING THE POTENTIAL FOR DEVELOPMENT OF THE UKRAINIAN REGIONS - ZVARYCH, Ihor; DMYTRYSHYN, Lesia; ZVARYCH, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Highlights the current issues of project management in the context of regional development. Using systematic and synergetic approaches, methods of analysis and synthesis, induction and deduction, comparative analysis, it is established that without proper organization of project management it is impossible to effectively use those financial resources invested in regional development. At the same time, the world has long known that their management system is a special area of modern management, the application of which gives tangible both current and future results. Every project in the process of implementation goes through various stages, which together are called its life cycle. And for the implementation of various functions of project management requires appropriate actions, defined as the processes of their management. At the same time, project management is an integrated process: actions (or lack thereof) in one direction affect other areas. This relationship forces a balance between project objectives – often improvement in one area can only be achieved through deterioration in another. At the same time, project management processes can be divided into six main groups, which implement different management functions: innovation, planning, implementation, analysis, management and completion. At the same time, the system of network planning and management methods should be singled out – a set of planning and management methods for economic development and research and development and design and technological work, new products, construction and reconstruction of buildings and structures, overhaul of fixed assets using network schedules used today in the national economу, which gives the opportunity to have a positive impact on the management of investment projects in Ukraine.
Keywords: region; investments; innovations; project; investment project; potencial; development